Cross-linkable polyethers as healing/sealing agents for self-healing of cementitious materials. (15th May 2016) - Araújo, Maria; Van Vlierberghe, Sandra; Feiteira, João; Graulus, Geert-Jan; Van Tittelboom, Kim; Martins, José C.; Dubruel, Peter; De Belie, Nele
Abstract: To date, the potential of several types of polymeric materials as healing agents for self-healing of concrete has already been investigated. Generally, for self-healing concrete with encapsulated polymeric healing agents, the curing mechanism is triggered upon contact with moisture/air or upon reaction with a second component provided by additional capsules. The present work explores the use of in-situ curable hydrogels formed as a result of the elevated pH of the cementitious matrix, via a Michael-type addition reaction, as potential healing/sealing materials for concrete applications. For this purpose, a variety of acrylate-endcapped urethane-based precursors were synthesized and combined with a thiol-based cross-linker. Various properties including the viscosity, the curing time, the swelling capacity and the cross-linking efficiency have been evaluated. The potential of the developed materials to seal concrete cracks was assessed through manual injection. The results indicate that the cross-linking reaction can readily occur in-situ due to the alkaline environment of the cementitious matrix and that the hydrogels exhibit favorable sealing properties. Graphical abstract: Highlights: In-situ curable polyethers are presented as healing agents for self-healing of concrete. Curing of the hydrogels could occur due to the alkaline environment of the cementitious matrix. Healing efficiency was evaluated by determining the regain in water tightness of the healed cracks. Water ingress into the crack was significantly decreased when crack repair was done with the PPG-based healing agent.